Hemodialyzed women — physical, psychological and social aspect of hemodialysis - Betke, Katarzyna; Banaszkiewicz, Mariola (Nursing Problems / Problemy Pielęgniarstwa, 2012)
A chronic renal insufficiency has a negative influence on every sphere of a women’s life — somatic, mental and social. Concomitant disease renders significant influence (income) on daily functioning person of to the end life. Young female patients storm arranged so the world wide plans and dreams, sometimes makes the chances of maternity, among the older forces of existing habits, social roles and lifestyles. Reduction in mood, apathy, anxiety, depression, changes the hierarchy of values, everyday behaviors, working life and social. In patient’s life are many significant changes: style of life, priorities, objectives and needs. These entire factors exercises clear brand on every sphere of human functioning. Worse mood and depression resulting from it make the therapeutic process more difficult — they become an obstacle in mobilising a patient to undertake actions that help her to adapt to a disease and to maintain physical fitness. The necessity of not yet filled out the roles of professional, social, or significant restriction results in a significant sense of failure and the same low level of self-esteem. Hemodialysis is one of the renal substitution treatment methods, mostly applied to renal chronic insufficiency therapy.